Studi Naqd Al-Ḥadīth atas Hadis ‘Āisyah tentang Mesjid tidak Halal bagi Perempuan Haid - H Rajab (Universitas Islam Negeri Alauddin, 2022)
This study intends to research the hadith of Aisyah ra. about the mosque is not lawful for menstruating women. This research is important because the need for women who are menstruating to enter and be in the mosque today is getting stronger, such as attending the Koran, studying and teaching, while there is an opinion that is still firmly held by the Muslim community to this day is that women who are menstruation are prohibited from entering the mosque. Some studies conclude that the hadith of 'Āisyah is daif because one of its narrators is considered majhūl. But is it true? This study attempts to re-examine Aisyah's hadith by using the methods and stages of research as described by M. Syuhudi Ismail, namely takhrīj al-ḥadīth, sanad research, matan research, and concluding. This is library research and analytical method using the theory of authenticity of hadith compiled by Ibn al-Ṣalāḥ. From the research conducted, it is known that the quality of the hadith 'Āisyah is Hasan. There is a problem with his sanad, namely with Aflat bin Khalīfah, because his personality did not get a perfect assessment from hadith critics, although it is not proven that he is majhul. From the perspective of hadith, there is no contradiction of this hadith with other traditions, because the traditions that are considered contradictory can be compromised through the al-jam'u wa al-taufīq method.